Māori Archaeology and History of Heretaunga, New Zealand Six Centuries of Power and Place - Allen, Mark W.; Tomoana, Ngahiwi; August, Stella; Moore, Wikitoria (Conflict, Environment, and Social Complexity, 2024)
XXI, 225 p. 53 illus., 18 illus. in color.